Elbow Overuse Injuries in Pediatric Female Gymnastic Athletes: Comparative Findings and Outcomes in Radial Head Stress Fractures and Capitellar Osteochondritis Dissecans. (15th September 2021) - Wilson, Philip L.; Wyatt, Charles W.; Searls, William C.; Carpenter, Connor M.; Zynda, Aaron J.; Vite, Lorenzo; Ellis, Henry B.
Abstract : Background: Radial head stress fractures (RHSFs) and capitellar osteochondritis dissecans (COCD) are rare but may be seen in gymnasts. The purpose of this study was to compare the clinical and radiographic characteristics and the outcomes of RHSF and COCD in pediatric and adolescent gymnastic athletes. Methods: Classical gymnasts and competitive tumblers ⩽18 years of age presenting with RHSF or COCD over a 5-year period were reviewed. Radiographic characteristics, clinical characteristics, and patient-reported outcomes were compared. Results: Fifty-eight elbows (39 with COCD and 19 with RHSF) were studied; the mean patient age was 11.6 years. Gymnastic athletes with RHSF competed at a higher level; of the athletes who competed at level ≥7, the rate was 95% of elbows in the RHSF group and 67% of elbows in the COCD group. The RHSF group presented more acutely with more valgus stress pain than those with COCD (p < 0.01) and demonstrated increased mean valgus angulation (and standard deviation) of the radial neck-shaft angle (13° ± 3.8° for the RHSF group and 9.3° ± 2.8° for the COCD group; p < 0.01) and decreased mean proximal radial epiphyseal height (3.7 ± 0.6 mm for the RHSF group and 4.2 ± 1.5 mm for the COCD group; p < 0.01). At a minimum of 2 years (range, 2.0 to 6.3 years), the RHSF group reported fewer symptoms; the QuickDASH (abbreviated version of the Disabilities of the Arm, Shoulder and Hand questionnaire) score was 1.75 ± 3.84 points for the RHSF group and 7.45 ± 7.54 points for the COCD group (p < 0.01). Those at a high level (≥7) were more likely to return to gymnastics independent of pathology, with the RHSF group reporting higher final activity levels with the mean Hospital for Special Surgery Pediatric Functional Activity Brief Scale (HSS Pedi-FABS) score at 26.0 ± 7.5 points compared with the COCD group at 23.6 ± 5.7 points (p < 0.05). Of the 9 patients with bilateral COCD, only 3 (33%) returned to gymnastics. Conclusions: RHSF with features similar to the more familiar COCD lesion may present in gymnastic athletes. Those with RHSF may present more acutely with a high competitive level and may have a better prognosis for return to competitive gymnastics than those with COCD. Level of Evidence: Prognostic Level III . See Instructions for Authors for a complete description of levels of evidence.